Decreased sirtuin 1 in type 2 diabetes patients with abnormal BMD - Xu, Yao; Hu, Tianxiao; Jiang, Peiwu; Wang, Xiujing; Yao, Jiaqi; Shen, Huiling; Zhang, Zhenying; Zheng, Bojing; Wang, Ting; Ren, Yanxia; Wang, Jing; Tan, Qingying (Frontiers in Endocrinology, 2025)
IntroductionSirtuin 1, a class III histone deacetylase, plays a critical role in the pathophysiology of both diabetes mellitus and bone metabolism by promoting osteoblast differentiation and inhibiting osteoclast maturation. However, its exact impact on bone mineral density (BMD) and bone metabolism in type 2 diabetes mellitus (T2DM) remains unclear. This study investigates the relationship between Sirtuin 1 levels, BMD, and bone metabolism in newly diagnosed T2DM patients, specifically examining alterations in Sirtuin 1 levels in those with concomitant osteoporosis or osteopenia.MethodsA total of 69 newly diagnosed T2DM patients and 82 control subjects with normal glucose tolerance (NGT) were enrolled. Serum Sirtuin 1 levels and bone turnover markers, including osteocalcin (OC), procollagen type 1 N-terminal propeptide (P1NP), and β-C-terminal telopeptide of type I collagen (β-CTX), were measured using enzyme-linked immunosorbent assay (ELISA). BMD was assessed via dual-energy X-ray absorptiometry (DXA). Comparisons of these parameters were made between the T2DM and NGT groups.ResultsT2DM patients were further categorized into a normal BMD group (DMn) and an osteopenia or osteoporosis group (DMo), and differences in Sirtuin 1 levels between these subgroups were analyzed. Risk factors for osteoporosis/osteopenia in T2DM patients were also evaluated. Serum Sirtuin 1 levels were found to be significantly diminished in the T2DM group relative to the control group (P < 0.05), with no significant differences in lumbar spine BMD, OC, 25(OH)D, and β-CTX between groups (P > 0.05). Osteoporosis incidence was higher in T2DM subjects compared to controls (34.8% vs. 18.3%, P = 0.026). Subgroup analysis revealed that SIRT1 levels in T2DM patients with osteoporosis or osteopenia exhibited a significant reduction compared to those with normal BMD (P < 0.05). Logistic regression indicated that Sirtuin 1, age, HDL-C, P1NP, and β-CTX were independent risk factors for osteoporosis in T2DM patients.DiscussionIn conclusion, decreased serum Sirtuin 1 levels are associated with bone turnover markers in T2DM patients and may serve as an independent risk factor and potential biomarker for diagnosing bone metabolism disorders in newly diagnosed T2DM patients.